ANALYZING STUDENTS’ ENGLISH-SPEAKING SKILLS USING SPEECHACE: INSIGHTS FROM AN AI-POWERED ASSESSMENT TOOL - Ningsih, Fitria (Pedagogic Research-Applied Literacy Journal, 2024)
AI technology has increasingly integrated into language learning and assessment, offering efficient and engaging environment. This study evaluated the effectiveness of Speechace, an AI powered language assessment tool, in improving speaking skills among first semester students through a mixed-method approach. The findings revealed an average overall performance score of 5.69 out of 9, with female students consistently outperforming males students in pronunciation, fluency, vocabulary, grammar and overall speaking competence. The question-specific analysis showed that students performed better on personal topics, exhibiting higher fluency and fewer pauses. Speechace provided valuable feedback, particularly in evaluating fluency-including the report of word per minute and bad pauses-as well as pronunciation accuracy via color-coded feedback. These findings highlight the potential use of AI tools in language education and offer insight for educators on integrating technology into English language instruction, more specifically in speaking skills.